Application of chemical compounds during pre-harvesting to control post-harvesting green mold in citrus - Kirinus, Marines Batalha Moreno; Dorneles, Keilor da Rosa; Silva, Pricila Santos; Barreto, Caroline Farias; Oliveira, Roberto Pedroso; Malgarim, Marcelo Barbosa (Semina: Ciências Agrárias, 2021)
This study aimed to evaluate the effect of system-acquired resistance inducing compounds applied during the pre-harvest of 'Navelina' orange and 'Ortanique' tangor in controlling post-harvest disease caused by Penicillium digitatum. The products applied were acibenzolar-s-methyl (ASM), imidacloprid (IMI), methyl jasmonate (MeJa), sodium selenite, potassium silicate, and thiamethoxam (TMT). Sterile distilled water was used as the control. The applications were administered 45, 30, and 15 days before harvesting. In 2015 and 2016, 840 fruits were randomly collected, and when they reached commercial maturation, they were sanitized, half were pierced with a needle in the equatorial region. The fruits were inoculated with a 10 ÂµL spore suspension (1 Ã— 106 conidia mL-1) of P. digitatum, in the equatorial region. The experiment was performed with three replicates, each comprising 10 fruits and repeated over two consecutive crop seasons. Disease incidence was evaluated on pierced (at 72 and 144 h after inoculation [hai]) and unperforated (at 360 hai) fruits. For pierced fruits, lesion expansion rate (rL), disease severity, expansion rate of sporulating area (rE), and sporulating area were evaluated. The area under the disease progress curve (AUDPC) and the area under the sporulating area progress curve were calculated. Both cultivars were susceptible; however, the rL and rE had lower values for 'Ortanique'. The tested products reduced the disease incidence in both cultivars. Potassium silicate reduced rL and rE, whereas sodium selenite reduced rE. The disease severity was reduced by potassium silicate, sodium selenite, and ASM. AUDPC was reduced by sodium selenite and potassium silicate treatments. Among the tested products, potassium silicate and sodium selenite applied during the pre-harvest of 'Navelina' orange and 'Ortanique' tangor had the highest reductions for disease incidence (ranging from 14% to 37%, respectively) and severity (60% and 70%, respectively), rE (50% for both compounds), and total sporulating area (55% and 56%, respectively), reducing the green mold in post-harvested fruits caused by P. digitatum.